Methodology development for measuring virtual university social responsibility (VUSR) - Esfijani, Azam (Curtin University, 2014)
This thesis addresses the most challenging issues in online education and its social responsibility. A world’s first ontology on virtual university social responsibility (VUSR) along with an ontological-driven approach for measuring the corporate social responsibility (CSR) for virtual universities (VUs) in five dimensions, namely education, research, engagement, ethics and transparency is developed. The impact on social, economic and ethical standards is ascertained by rigorously defining measurement indicators and performance assessment attributes to help assess CSR.